Impedance spectroscopy and dielectric anisotropy-type analysis in dye-doped nematic liquid crystals having different preliminary orientations - Okutan, M; Yakuphanoğlu, Fahrettin; San, SE; Koysal, O (Elsevier, 2005)
Reorientation tendencies of liquid crystal (LC) molecules are investigated for two different fundamental orientation configurations known as homogeneous (HG) and homeotropic (HT). Dielectric anisotropy properties of a HT sample and a HG one are investigated as a function of frequency. The dielectric anisotropy changes from the positive type to the negative type. The obtained results suggest that the samples exhibit dielectrically controlled positive dielectric anisotropy (p-type Delta epsilon) with a critical frequency transition to negative dielectric anisotropy (n-type Delta epsilon) behavior. The high-frequency relaxation process exhibits non-Debye-type behavior due to dipolar rotation around the long molecular axis. The orientation configurations (HG and HT) change the dielectric anisotropy properties of the LC in a favorable manner. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: liquid crystals; dielectric anisotropy; homogeneous; homeotropic; molecular reorientation